Green synthesis of silver doped zinc oxide nanoparticles using fresh leaf extract Morinda citrifoliaand its antioxidant potential. (2021) - Shreema, K.; Mathammal, R.; Kalaiselvi, V.; Vijayakumar, S.; Selvakumar, K.; Senthil, K.
Abstract: A green synthesis approach has been employed to synthesize silver doped zinc oxide (Ag-ZnO) nanoparticles from the fresh leaf extract of Morinda citrifolia using a simple co-precipitation method. The synthesized nanoparticles are investigated using FTIR, XRD, UV–Visible, SEM and antioxidant analysis. FTIR spectra displayed characteristic peaks related to ZnO. The formation of hexagonal crystal structure for the synthesized nanoparticles is confirmed from the XRD analysis. The calculated band gap energy is found to be decreased for the Ag-ZnO nanoparticles. The surface morphology analyzed using SEM indicated that pure ZnO nanoparticles synthesized without using the leaf extract are more agglomerated whereas the Ag-ZnO nanoparticles synthesized using the leaf extract are almost spherical in shape with less agglomeration. A maximum radical scavenging activity of 83% is observed for the green synthesized Ag-ZnO nanoparticles.